AZIZIDDIN NASAFI ON UNIVERSE AND IT’S CLASSIFICATION (World Bulletin of Social Sciences, 2025)
The article elaborates the ideas of Aziziddin Nasafi which had impacted on the posterior view on universe and it’s classification. The influence of Aziziddin Nasafi on the later scholars are analysed from the viewpoint of comparative eschatology